Case Report: complete response to preoperative ipilimumab and nivolumab combination therapy in advanced papillary renal cell carcinoma with inferior vena cava tumor thrombus and multiple metastases - Nagahisa, Chika; Yoshida, Kazuhiko; Nozaki, Shuhei; Mizoguchi, Shinsuke; Fukuda, Hironori; Kobari, Yuki; Iizuka, Junpei; Nagashima, Yoji; Ishida, Hideki; Takagi, Toshio (Frontiers in Oncology, 2025)
IntroductionCombination therapy comprising ipilimumab and nivolumab is a safe and effective treatment for advanced renal cell carcinoma (RCC). However, its use in papillary RCC (pRCC) with an inferior vena cava (IVC) tumor thrombus extending to the right atrium has not been reported. Herein, we describe a case of pRCC with an IVC tumor thrombus extending to the right atrium and multiple metastases, which was effectively treated with combination therapy comprising ipilimumab and nivolumab.MethodsA 74-year-old man was diagnosed with pRCC based on a computed tomography-guided biopsy of a left renal tumor. The tumor extended to the right atrium and was accompanied by metastases to the pancreas, retroperitoneum, lymph nodes, bones, and lungs (cT3cN2M1). Based on the International Metastatic Database Consortium risk classification, the case was categorized as poor risk. Therefore, combination therapy comprising ipilimumab and nivolumab was initiated.ResultsNine months after initiating treatment, all metastases had disappeared, enabling open cytoreductive nephrectomy that had been deferred. Histopathological analysis revealed necrosis in most of the tumor tissue, with no viable cells in the primary tumor and IVC tumor thrombus. At 24 months postoperatively, the patient remained recurrence-free.DiscussionThis case highlights the potential efficacy of preoperative combination therapy with ipilimumab and nivolumab in advanced pRCC with IVC tumor thrombus and distant metastases. The treatment achieved a complete response and allowed successful surgical resection, suggesting its potential as a viable option in similar cases.